Outsourcing via reverse auction with a built-in menu of change orders - Elmar G. Wolfstetter (Bulletin of Economic Research, 2022)
Many firms invent and design products while outsourcing their production to independent contractors. We consider a dominant strategy mechanism that selects a contractor using a reverse auction, combined with a menu of permitted change orders from which the contractor can choose after updated cost information has become available. That mechanism maximizes the gain from trade, allows the firm to extract the second highest surplus, and induces the contractor to make efficient adjustments to output after updated cost information has~emerged.
Keywords: 330; auctions; change orders; mechanism design; outsourcing; procurement